Research on the visual/inertial integrated carrier landing guidance algorithm. (10th April 2018) - Meng, Yue; Wang, Wei; Ding, Zhenxing
In this article, we describe a visual/inertial integrated carrier landing guidance algorithm for aircraft carrier landing operations. The airborne vision system and the inertial navigation system are employed as sensors to obtain feature points of carrier runway as well as the aircraft inertial measurements. In this algorithm, visual and inertial information are integrated, and the Pose from Orthographic Projection and Scaling with Iterations algorithm is utilized to estimate aircraft position and carrier motion. A simulation was constructed validating this algorithm, and the results of this simulation show satisfactory accuracy as well as high efficiency in carrier landing guidance.